Interstitial-driven local chemical order enables ultrastrong face-centered cubic multicomponent alloys. (15th January 2023) - He, Zhufeng; Guo, Yanxin; Sun, Lifang; Yan, Hai-Le; Guan, Xianjun; Jiang, Shuang; Shen, Yongfeng; Yin, Wen; Zhao, Xiaoli; Li, Zhiming; Jia, Nan
Abstract: Multicomponent alloys of the Fe-Mn-Co-Cr-Ni family with face-centered cubic (fcc) structure exhibit many excellent properties. However, they usually show limited yield strength, which cannot meet the demand for practical applications. Here, we report a universal strategy for designing ultrastrong and ductile fcc multicomponent alloys, by introducing interstitial-driven local chemical order (LCO) through simple thermomechanical processing. In a prototype FeMnCoCrN multicomponent alloy processed by partial-recrystallization annealing, a high-density of fine laths containing interstitial-driven LCO domains (with both short- and medium-range orders) are predominant. Those laths evolve from planar dislocation slip bands promoted by the intrinsic short-range order of the alloy under prior cold deformation. Owing to the hardening effect of the LCO-laths, an ultra-high yield strength of 1.34 GPa is achieved, while deformation twinning contributes to a uniform elongation of 13.9%. This design strategy, which is also successfully verified in a multicomponent austenitic steel, provides a new paradigm for developing high-performance fcc materials at low cost. Graphical abstract: We propose an effective strategy for designing ultrastrong and ductile fcc multicomponent alloys, by introducing interstitial-driven local chemical order (LCO) through simple thermomechanical processing. The ultra-high yield strength benefits from profuse fine laths containing the LCO domains. This strategy, also verified in a multicomponent austenitic steel, provides a novel and universal paradigm for developing high-performance fcc materials at low cost. Image, graphical abstract